2014
DOI: 10.1007/s00417-014-2573-y
|View full text |Cite
|
Sign up to set email alerts
|

Early postoperative changes of the foveal surface in epiretinal membranes: comparison of 23-gauge macular surgery with air vs. balanced salt solution

Abstract: The analysis of early contour changes after ERM surgery was technically possible. Long-term data have to be looked at before the clinical impact of this methodology can be estimated. Although there were no big differences between both groups (AIR vs. BSS), this could change within a longer and more representative follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 19 publications
0
18
1
4
Order By: Relevance
“…Possibly, additional concomitant intravitreal antiinflammatory therapy, such as triamcinolone, may reduce this risk. Leitritz et al (2014) focused on foveal surface symmetry analysis in their retrospective study, with significantly lower values for the BSS group. Beside that main outcome they stated comparable vision results for BSS and air, but with more improvement in VA in the air group (not significant difference between air and BSS).…”
Section: Improvement In Vision Totalmentioning
confidence: 99%
See 3 more Smart Citations
“…Possibly, additional concomitant intravitreal antiinflammatory therapy, such as triamcinolone, may reduce this risk. Leitritz et al (2014) focused on foveal surface symmetry analysis in their retrospective study, with significantly lower values for the BSS group. Beside that main outcome they stated comparable vision results for BSS and air, but with more improvement in VA in the air group (not significant difference between air and BSS).…”
Section: Improvement In Vision Totalmentioning
confidence: 99%
“…We did not randomize the status of the lens prior to surgery, because main goal of our study was randomizing characteristics of preoperative retinal morphology (retinal thickness and intraretinal cystoid changes). Leitritz et al (2014) did not randomize for the lens status either, due to the retrospective study design; therefore, outcomes of statistical analysis of VA results should be handled with care. A surprising result when analyzing postoperative intraretinal cystoid changes among our patients having received BSS or air at the end of surgery was the trend for more postoperative intraretinal cystoid changes in the air group.…”
Section: Improvement In Vision Totalmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to a positive correlation between outer segment restoration and functional results after macular surgery, Itoh and associates observed that a recovery of the foveal cone microstructure may be seen as late as 12 months after anatomically successful surgery and that intact cone outer segment tips after ERM surgery correlate with BCVA [ 12 , 21 ]. The influence of the used tamponade in the end of ERM surgery (air or balanced salt solution) has also been discussed [ 23 ].…”
Section: Discussionmentioning
confidence: 99%